2022
DOI: 10.1002/celc.202200091
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Phenol from Water in the Presence of NaCl in Undivided Cells Equipped with Carbon Felt or Ni Cathodes: Effect of Air Pressure

Abstract: Recently, the electrochemical treatment of wastewater polluted by recalcitrant organics and containing chlorides was shown to be significantly improved adopting proper operative conditions such as suitable anodes and cathodes and low current density. In particular, the use of suitable cathodes such as carbon felt or silver could increase the removal of TOC and reduce the formation of chlorinated by-products. In this study, attention was focused on the utilization of carbon felt cathodes with the main aim to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…It recently has been shown that EF can strongly benefit from the utilization of pressurized air 17‐19,21‐23 and relatively low values of working potential and current density 18,19 . Hence, a series of electrolyses was carried out using a CF cathode, Ti/Ta 2 O 5 ‐IrO 2 anode, and different air pressures (1, 5 and 10 bar) and current densities (10 and 60 mA cm −2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It recently has been shown that EF can strongly benefit from the utilization of pressurized air 17‐19,21‐23 and relatively low values of working potential and current density 18,19 . Hence, a series of electrolyses was carried out using a CF cathode, Ti/Ta 2 O 5 ‐IrO 2 anode, and different air pressures (1, 5 and 10 bar) and current densities (10 and 60 mA cm −2 ).…”
Section: Resultsmentioning
confidence: 99%
“…When the electrolysis was repeated with a pressure of 10 bar, a removal of TOC ≈38% was obtained. According to the literature, the remarkable effect of pressure on the performance of EF is due to the fact that a higher air pressure results in higher solubilities of oxygen, thus increasing the generation of H 2 O 2 and consequently that of hydroxyl radicals 17,19,21‐23 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations